Implementation of Interactive Learning Model Based on Learning by Asking with the Assistance of Virtual Mentors to Improve Learning Outcomes Students - Mellyta Uliyandari; Nirwana; Nurlia Latipah (Postgraduate, University of Mataram, 2023)
This research aims to apply an interactive learning model based on asking questions with the use of a virtual mentor. The method used in this research is quasi-experimental. The research results showed that the validation scores for interactive learning media by material experts and media experts were respectively 72 and 58 in the very appropriate category. The results of learning media readability test were 82.18 in the very good category. The pretest result of students in control class was 48.6 while the posttest was 73.68. Experimental class, pretest score was 49.87 and posttest score was 80.76. The N-gain values ​​for the control and experimental classes are 0.48 and 0.61 respectively. Based on the research results, it is known that student learning outcomes increased in both the control and experimental classes, but the increase in the experimental class was higher than in the control class. This is because the experimental class uses an interactive learning model based on learning to ask questions assisted by a virtual mentor. The conclusion of this research is that the implementation of an interactive learning model based on learning by asking with the help of a virtual mentor is effective in improving student learning outcomes.